Granulomas as the Most Useful Histopathological Feature in Distinguishing between Crohn's Disease and Intestinal Tuberculosis in Endoscopic Biopsy Specimens - Ye, Ziyin (Medicine (Baltimore), 2015)
The incidence of Crohn's disease (CD) is increasing in Chinese populations in whom intestinal tuberculosis (ITB) is prevalent. This study aimed to identify differential diagnostic microscopic and endoscopic characteristics of CD from those of ITB. Patients with CD (N = 52) and patients with ITB (N = 16) diagnosed between 2010 and 2013 were identified. Specimens obtained via endoscopy were analyzed microscopically by a pathologist. The relationship between endoscopic appearance and histopathological features was analyzed. The χ(2) test, Fisher's exact probability test, and the Mann-Whitney U test were used. Granulomas were present in 81.3% of ITB cases and in 67.3% of CD cases (P = 0.36). Granulomas in ITB cases were denser than those in CD cases (mean 5.29 ± 4.30 vs. 2.46 ± 3.50 granulomas per 10 low power fields; each low power field = 3.80 mm(2); P = 0.005). Granulomas in ITB cases were larger (mean widest diameter, 508 ± 314 μm; range, 100–1100 μm) than those in CD cases (mean widest diameter, 253 ± 197 μm; range, 50–800 μm). Basal plasmacytosis was more common in CD cases than in ITB cases (77.0% vs. 37.5%, P = 0.000). Endoscopy findings such as longitudinal ulcer, aphthous ulcer, and cobblestone appearance were only seen in CD cases (34.6%, 21.2%, and 23.1%, respectively). Granulomas were detected in the majority of cases with longitudinal ulcers (88.9%). Basal plasmacytosis was exclusively detected in cases with longitudinal ulcer and a cobblestone appearance. Characteristics of granulomas maybe the most important distinguishing features between CD and ITB. However, the histopathological characteristics of both diseases may overlap on endoscopic biopsy specimens. An accurate diagnosis should be made that considers clinical, endoscopic features, and pathologic findings.